2009
DOI: 10.1080/08820130802307294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the CCR5-Δ32 Mutation on Hepatitis C Virus-Specific Immune Responses in Patients with Haemophilia

Abstract: In hepatitis C virus (HCV) infection antiviral T cells express the CC chemokine receptor 5 (CCR5). Their recruitment to the liver is an important step in the immune response. A 32 base pair deletion in the CCR5 gene leads to reduced expression and total loss of CCR5 in CCR5-n32 heterozygous and homozygous subjects, respectively. However, the role of this mutation for antiviral immunity remains unclear. Here, we analysed proliferation, IFN-gamma and IL-4 secretion (ELISpot) induced by the HCV antigens core, NS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the context of persistence/resolution of HCV infection and viral control, in the one hand, studies described association of the CCR5Δ32 allele with reduced rates of spontaneous viral clearance (Nattermann et al, 2011;Morard et al, 2014), higher viral load (Yilmaz et al, 2014), and reduced anti−HCV immune response (Ahlenstiel et al, 2009). On the other hand, studies have reported association between the CCR5Δ32 variant and increased rates of spontaneous viral clearance (Goulding et al, 2005;El-Moamly et al, 2013).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…In the context of persistence/resolution of HCV infection and viral control, in the one hand, studies described association of the CCR5Δ32 allele with reduced rates of spontaneous viral clearance (Nattermann et al, 2011;Morard et al, 2014), higher viral load (Yilmaz et al, 2014), and reduced anti−HCV immune response (Ahlenstiel et al, 2009). On the other hand, studies have reported association between the CCR5Δ32 variant and increased rates of spontaneous viral clearance (Goulding et al, 2005;El-Moamly et al, 2013).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Moreover, Ahlenstiehl et al could show a significantly decreased HCV-specific IFN-γ response of CD8(+) T-cells in carriers of the CCR5Δ32 allele as compared to cells from patients with a homozygeous wildtype genotype. This finding suggests the CCR5Δ32 polymorphisms to possibly affect cellular immune responses in HCV infection [43]. …”
Section: Hcv and Ccr5δ32mentioning
confidence: 99%
“…However, no association of different CCR5 gene alleles with viral persistence was found in several other cohorts [104, 109, 111, 112]. A recent study addressed the effects of CCR5delta32 mutation on HCV specific T cell responses [113]. IFN-γ responses were reduced in patients carrying the mutation but other T cell functions (migration, proliferation, IL-4 production) were not altered.…”
Section: Reviewmentioning
confidence: 99%